Antibacterial properties of poly (octanediol citrate)/gallium-containing bioglass composite scaffolds - Zeimaran, E.; Pourshahrestani, S.; Djordjevic, I.; Pingguan-Murphy, Belinda; Kadri, Nahrizul Adib; Wren, A.W.; Towler, M.R. (Kluwer (now part of Springer), 2016)
Bioactive glasses may function as antimicrobial delivery systems through the incorporation and subsequent release of therapeutic ions. The aim of this study was to evaluate the antimicrobial properties of a series of composite scaffolds composed of poly(octanediol citrate) with increased loads of a bioactive glass that releases zinc (Zn2+) and gallium (Ga3+) ions in a controlled manner. The antibacterial activity of these scaffolds was investigated against both Gram-positive (Staphylococcus aureus) and Gram-negative (Escherichia coli) bacteria. The ability of the scaffolds to release ions and the subsequent ingress of these ions into hard tissue was evaluated using a bovine bone model. Scaffolds containing bioactive glass exhibited antibacterial activity and this increased in vitro with higher bioactive glass loads; viable cells decreased to about 20 % for the composite scaffold containing 30 % bioactive glass. The Ga3+ release rate increased as a function of time and Zn2+ was shown to incorporate into the surrounding bone.